Da luta pela Politecnia à reforma do ensino médio: para onde caminha a formação técnica integrada ao ensino médio - Amorim, Gilberto José de (2018)
This research has as its theme the study of the technical training integrated to the high school proposed by law 11.892 / 08 that created the Federal Institutes of Education, Science and Technology. Within this theme, we sought to understand the conceptions of integrated training of teachers working in the agricultural technical course of IFSP / Barretos, as well as the professional profile the course seeks to train, seeking to associate them with the predominant ideological tendencies. In this sense, the work demonstrated the existence of a dispute between the subjects about which educational emphasis should prevail in the students' teaching process. Through the research, a historical retrospective was also carried out in order to analyze the objectives of Brazilian legislators with successive reforms of the Brazilian educational system. Furthermore, the consequences of the reform of secondary education in the process of consolidating integrated training from the viewpoint of the local community, as well as the social movements and representatives of power, were investigated. For the construction of this work it was necessary a bibliographical and documentary analysis, besides interviews with representatives of the power and of social and / or academic movements. To understand how each teacher stands on the subject, the speeches given by the subjects were seen as statements. They were obtained through questionnaires and interviews applied in the second half of 2017. From this perspective, this work allowed a reflection on the role of the federal institutes in the construction of an integrated training beyond the duality training of labor or propaedeutic training. Thus, the work pointed to the need to create conditions for the theoretical-political debate on the presuppositions of an integrated teaching and its pedagogical developments.